2014 IEEE International Conference on Computational Intelligence and Virtual Environments for Measurement Systems and Applicati 2014
DOI: 10.1109/civemsa.2014.6841436
|View full text |Cite
|
Sign up to set email alerts
|

An incremental framework for classification of EEG signals using quantum particle swarm optimization

Abstract: Classification of electroencephalographic (EEG) signals is a sophisticated task that determines the accuracy of thought pattern recognition performed by computer-brain interface (BCI) which, in turn, determines the degree of naturalness of the interaction provided by that system. However, classifying the EEG signals is not a trivial task due to their nonstationary characteristics. In this paper, we introduce and utilize incremental quantum particle swarm optimization (IQPSO) algorithm for incremental classific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…They compared the performance of IQPSO against ten other classifiers on two EEG datasets. The results suggested that IQPSO outperformed other classifiers in terms of classification accuracy, precision and recall [18].…”
Section: A the Classification Studies On Eeg Eye State Medical Datasetmentioning
confidence: 88%
“…They compared the performance of IQPSO against ten other classifiers on two EEG datasets. The results suggested that IQPSO outperformed other classifiers in terms of classification accuracy, precision and recall [18].…”
Section: A the Classification Studies On Eeg Eye State Medical Datasetmentioning
confidence: 88%
“…Other algorithms like Ant Colony Optimization (ACO) [34] or Particle Swarm Optimization (PSO) [35] have also been used. Adaptive approaches have been employed as well, like the auto-reinforced system introduced in [36], by incorporating a fed-back PSO and a rule-based classifier.…”
Section: Related Workmentioning
confidence: 99%
“…Classes with more training objects will have a higher tendency to influence the overall prediction. Thus, instead of using the FIFO approach, it is recommended to identify and store only the significant objects while eliminating the rarely used objects [16] for biometric authentication modelling.…”
Section: Literature Reviewmentioning
confidence: 99%